(Post)Feminist Genealogies in Kate Muir’s Suffragette City ad Lisa Evans’ Old Baggage - Mariana Ripoll Fonollar (Revista Alicantina de Estudios Ingleses)
This article explores Kate Muir’s Suffragette City and Lisa Evans’ Old Baggage didactic potential based on the interactions between women that belong to different (feminist) generations taking place in both novels. Suffragette City reproduces the conversations and encounters between the ghost of a Scottish suffragette fighting for her enfranchisement in the twentieth century, and her great-great-granddaughter living in New York at the beginning of the following century. Old Baggage also deploys the figure of the suffragette, but in this case, embodied by a Londoner in her fifties who has just been granted the right to vote, and a group of newly enfranchised girls. I argue that the intergenerational exchanges between an older suffragette and younger female characters metaphorically facilitate a dialogue between feminism and postfeminism illuminating the tensions and convergences between them. My reading of these novels is supported by what Stéphanie Genz calls the “genealogical approach” (2021) to postfeminism, which does not present both movements as dichotomous but acknowledges that different feminist moments should be understood as interrelated and not superseding each other in apparently distinctive “waves.” My ultimate aim is to present Suffragette City and Old Baggage as didactic texts which reflect on what I refer to as (post)feminist debates to vindicate the pertinence of feminism in a so-called postfeminist context.